Role of beta-arrestin 2 downstream of dopamine receptors in the basal ganglia - Thomas eDel'Guidice; Morgane eLemasson; Jean-Martin eBeaulieu (Frontiers Media S.A., 2011)
Multifunctional scaffolding protein beta-arrestins (βArr) and the G protein receptor kinases (GRK) are involved in the desensitization of several G protein coupled-receptors (GPCR). However, arrestins can also contribute to GPCR signaling independently from G proteins. In this review, we focus on the role of βArr in the regulation of dopamine receptor functions in the striatum. First, we present in vivo evidence supporting a role for these proteins in the regulation of dopamine receptor desensitization. Second, we provide an overview of the roles of βArr-2 in the regulation of ERK/MAPkinases and Akt/GSK3 signaling pathways downstream of the D1 and D2 dopamine receptors. Thereafter, we examine the possible involvement of βArr-mediated signaling in the action of dopaminergic drugs used for the treatment of mental disorders. Finally, we focus on different potential cellular proteins regulated by βArr-mediated signaling which could contribute to the regulation of behavioral responses to dopamine. Overall, the identification of a cell signaling function for βArr downstream of dopamine receptors underscores the intricate complexity of the intertwined mechanisms regulating and mediating cell signaling in the basal ganglia. Understanding these mechanisms may lead to a better comprehension of the several roles played by these structures in the regulation of mood and to the development of new psychoactive drugs having better therapeutic efficacy.